Strategies Used in Teaching Reading at Two Senior High Schools in Surabaya - Lydia Yanson (Widya Mandala Surabaya Catholic University, 2011)
This study was intended to know the teaching strategies that were used by English teachers in teaching reading and the students’ responses on those strategies at two Senior High Schools in Surabaya. It was a classroom observational research. The subjects of this study were English teachers and students of two private high schools in Surabaya. Their classroom activities were recorded by using a handy camera and a tape recorder and she also took some pictures by using a camera. Then, the teachers were interviewed to give comments about actions taken in classroom. The interviews were carried out after the observation. From the observations and interviews, the writer found out that the teachers have already used the appropriate strategies of teaching reading as suggested by the 2006 curriculum. For example: the teachers applied BKoF (Building Knowledge of Field) in pre-reading activities, MoT (Modeling of Text) in whilst-reading activities, JCoT (Joint Construction of Text) and ICoT (Independence Construction of Text) in post-reading activities. However, on a closer examination, the students responded differently on the teachers’ strategies. There were positive and negative responses from the students